Design strategies to define the architectural parti during problem solving | Estratégias de projeto para definir o partido arquitetônico durante a solução de problemas - Florio, Wilson; Mateus, Rafael Peres (Oculum Ensaios, 2020)
Based on video/audio design protocols, this paper aims to analyze the definition of the architectural parti in the design process. Video recordings occurred between the years of 2011 and 2012, and involved three active experienced architects who had their own studios. All architects were experienced designers and developed a single-family residence during one hour based on the same briefing. Each design process was taped with two cameras: one focusing on the actual drawing production, and the other on the architects, so as to register all their actions during the process. There was an accurate registry of the drawing and pause instances, aiming to provide an interpretation of each architect’s design procedure in the development of the architectural parti. This registry contributed to present a graphic representation of the design process frequency showing the time in which designers conceived the parti core. Architects were also interviewed, and their resulting designs were compared beholding the following parameters: (i) Site occupation x topography x open areas; (ii) Sectorization and functionality; (iii) Geometry and volume. The results obtained suggest that self-imposed restraints play an important role in the definition of the architectural parti, confirming this paper contribution to the comprehension of strategies used in the architectural design